Active crack control approach applied to a horizontal rotating machine. (May 2023) - Leão, Leandro de S; Pereira, Iago A; Carvalho, Felipe C; Cavalini, Aldemir A; Steffen, Valder
The present contribution proposes an active vibration control technique devoted to shafts with cracks aiming to minimize their propagation. The existence of a crack in rotating shafts can be characterized by 2 X and 3 X super-harmonic amplitudes in the vibration responses of the rotor, which can increase as the crack propagates along the shaft's cross-section. A proportional-integral-derivative control technique is applied to suppress the 2 X and 3 X vibration amplitudes of a cracked shaft, which is performed by using a bandpass filter applied to the vibration responses of the rotor. Numerical and experimental results are obtained through both a representative finite element model of a horizontal rotor and its corresponding test-rig. In this case, electromagnetic actuators are used to apply the control effort to the rotor. The Mayes model is applied for simulating the breathing behavior of the transverse crack. The linear fracture mechanics theory is considered to correlate the crack depth with the corresponding additional rotor flexibility. Both numerical and experimental results demonstrate the possibility of reducing the effects of a transverse crack through active control on the dynamic behavior of a rotating machine. Moreover, it is shown that the proposed control law is capable of controlling the crack effects with the rotor operating in different rotation speeds.